Making waves - Fang, Vicky (Fang, Vicky. Layla and the Bots, 2022)
Layla and the Bots visit the Surfside Rescue Center, where they meet a dolphin named Splash, who will only eat when the music is playing, but is very picky about the music--so Layla and the Bots build a machine that uses the sound waves Splash communicates with to change the music.